Typologies of organic beef farms in Catalonia - López-i-Gelats F.; Bartolomé J. (The contributions of grasslands to the conservation of Mediterranean biodiversity, 2010)
Organic livestock farming is going through remarkable increase in the last decades in Europe. This is also the case in Catalonia. However, little work has been done explicitly on the characteristics of the livestock farms undertaking to organic production. In order to filling this lacuna, the nature of organic beef farms has been examined in Catalonia. In 2008 structured interviews to farmers were conducted (n=37, being 16 percent of the total number of organic beef farms) and data was submitted to PCA and Cluster Analysis. The aim of this study is to characterise the organic beef farms to disclose the different management and adjusting strategies being carried out. Three typologies of organic beef farms have been distinguished: a first group characterised by young farmers with an intensive management (24 percent); a second group of motivated farmers to produce organically that have the continuity of the farming activity guaranteed (27 percent); and finally a third group of discouraged farmers that see their continuity threatened (49 percent). Results suggest that half of the organic beef farms in Catalonia convert to organic production manly for financial reasons, to continue with the farming activity.
13. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM International Network for the Research and Development of Pasture and Forage Crops, 2010/04/07-10, Alicante (Spain)